Nilai Religius dalam Novel Assalamu’alaikum Baitullah Karya Asma Nadia: Religious Values In The Novel Assalamu’alaikum Baitullah By Asma Nadia - Putri, Lutfia; Suntoko, Suntoko; Hartati, Dian (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This research is motivated by shifts in increasingly complex religious values. The widespread news regarding the phenomenon of excessive selfies during the Umrah pilgrimage illustrates a shift in religious values. This research aims to describe the religious values ​​contained in the novel Assalamu'alaikum Baitullah by Asma Nadia. The method used is qualitative with descriptive data analysis techniques. This research uses two data collection techniques, namely observation techniques and literature study techniques. Primary data was obtained from the novel Assalamu'alaikum Baitullah by Asma Nadia and secondary data was obtained from various relevant sources. The theory used is the Atmosuwito religious value theory. The results of the research show that there are six aspects of religious values ​​in the novel Assalamu'alaikum Baitullah by Asma Nadia, namely; 1) surrender, submission, and obedience, 2) a life full of glory, 3) inner feelings of connection with God, 4) feelings of sin, 5) feelings of fear, and 6) recognizing the greatness of God. Novels that contain religious values, if studied, can influence someone to apply religious values ​​in everyday life. This research will be recommended as module type printed teaching material for second semester high school students in class XII.